Carotid intimal medial thickness predicts cognitive decline among adults without clinical vascular disease - Wendell, Carrington Rice; Zonderman, Alan B; Metter, E Jeffrey; Najjar, Samer S; Waldstein, Shari R (Stroke (1970), 2009)
Though clinical cardiovascular and cerebrovascular diseases are established risk factors for cognitive decline and dementia, less is known about the relations between vascular health and cognition among individuals without these diseases. Carotid intimal medial thickness (IMT), a measure of subclinical vascular disease, is associated with concurrent decrements in cognitive function, but relatively little research has examined longitudinal relations between carotid IMT and prospective cognitive decline. We examined relations of carotid IMT to prospective trajectories of cognitive function among 538 (aged 20 to 93, 39% male, 66% white) participants in the Baltimore Longitudinal Study of Aging (BLSA) free of known cardiovascular, cerebrovascular, and neurological disease. Participants underwent initial carotid ultrasonography and repeat neuropsychological testing on up to 8 occasions over up to 11 years of follow-up. Mixed-effects regression analyses were adjusted for age, gender, race, education, mean arterial pressure, body mass index, total cholesterol, smoking, depressive symptoms, and cardiovascular medication use. Individuals with greater carotid IMT displayed accelerated decline in performance over time on multiple tests of verbal and nonverbal memory, as well as a test of semantic association fluency and executive function. Carotid IMT predicts accelerated cognitive decline, particularly in the domain of memory, among community-dwelling individuals free of vascular and neurological disease.